A new computer application for teaching sexual history taking to medical students: innovation and evaluation in the UfaceMETM program - Ross MW; Ayers J; Schmidt W; Bugbee TW; Knight J; Muthyala BK; Newstrom NP (Advances in Medical Education and Practice, 2019)
Michael W Ross,1 James Ayers,2 William Schmidt,2 Thomas W Bugbee,2 Joan Knight,2 Brian K Muthyala,3 Nicholas P Newstrom11Program in Human Sexuality, Department of Family Medicine, University of Minnesota Medical School, Minneapolis, MN 55454, USA; 2UfaceME, Minneapolis, MN 55416, USA; 3Division of General Internal Medicine, University of Minnesota Medical School, Minneapolis, MN 55455, USABackground: We developed an app (UfaceME) which simultaneously allows patient and clinician to be viewed on a split screen, then replayed and rated on a series of semantic differential scales and the ratings of the clinician of their own response to the interview, and the patient’s response, displayed on a graph.Method: We evaluated the app with trials with 14 medical student volunteers who alternated the roles of patient and clinician, using 2 randomly allocated sexual case histories. Semantic differentials for 10 adjectives were examined pre- and post-exercise. There were significant differences in 8 of the 10 adjectives. A focus group with the 14 subjects was also carried out and transcribed. The exercise was repeated with all 175 first-year medical students taking a sexual history.Results: Qualitative data indicated themes of being surprised and educated by non-verbal and verbal responses; seeing how the patient rated their responses; rating and watching discomfort; differences in clinician/patient perceptions and response; and the advantage of feedback. Quantitative data comparing self vs “patient” showed low correlations between perceptions of being “at ease”, moderate for appearing “distracted”, and high for appearing “engaged”.Conclusion: UfaceME was easily understood and used, and the opportunity to replay and rate performance on key semantic scales, and watch and assess verbal and non-verbal performance, including patient rating, provided valuable insight.Keywords: sexual history, interview skills app, medical students, training feedback